PENGECUALIAN PERJANJIAN HAK KEKAYAAN INTELEKTUAL DALAM HUKUM PERSAINGAN USAHA - Dani Amran Hakim (Fiat Justisia: Jurnal Ilmu Hukum, 2015)
Law business competition in the country Indonesia know the exceptions  to assert that a the rule of law expressed does not apply for those kind certain agents or behavior particular activity. Law competition business environment in general grant an exemption on the basis of agreement , for example agreement intellectual property rights (IPR). IPR is incentives and reason was given the right monopolizes and protection because IPR need resources and time in an effort to get it, based on article 50 alphabet b Law on Business Competition. An exemption based on article 50 alphabet b Law on Business Competition the elaborated competition supervisory commission by issuing commission rules business competition supervisory Law Number 2 of 2009 on Exceptions The Application of the Law Number 5 of 1999 on Prohibition of Monopoly and Unfair Business Competition of a Pertaining to Intellectual Property Rights Scope arrangement based on Commission Rules Business Competition Supervisory Number 2 of 2009 is: (1) the license agreement that is in scope patent, the right brand, copyright, the right industrial design, the right design the layout integrated circuit and the right trade. (2) Trademark and brand services. (3) the design layout integrated circuit. Keywords: Exeptions, Intellectal Property Rights, Business Competition Law